Pelatihan GeoGebra untuk Mata Pelajaran Geometri di MGMP Matematika SMA Kabupaten Purbalingga - Nunung Nurhayati; Siti Rahmah Nurshiami; Renny; Rina Reorita; Sri Maryani (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Teachers as educators are required to be able to keep up with technological advances, this is in line with the Republic of Indonesia Law no. 14 of 2005 in term of improving the professional competence of teachers. The Covid-19 pandemic has brought changes in term of interacting with technology. It has a positive impact on teachers as educators. For mathematics teachers, the development of technology has become a strategy to introduce a mathematical applications not only to understand but also to obtain the applications. One of the applications that strongly support learning mathematics is the GeoGebra application. This application can provide a mathematical visualization so that teachers as educators and students as learners will more easily to understand mathematical topic more deeply. Some mathematical subjects require visualization to make it easier to understand, for example geometry subject especially in space. This subject is introduced at the beginning in senior high school level. This subject need reasoning, visualization, and imagination to understand the geometric shape. GeoGebra application can improve the reasoning and imagination of students. This community service team provides GeoGebra training for high school mathematics group which called MGMP of Mathematics in Purbalingga Regency especially in Geometry subject. First of all, MGMP of Mathematics in Purbalingga Regency were given a pre-test and post-test regarding their initial knowledge of GeoGebra from 35 trainee of mathematics teachers in Purbalingga Regency. The results of pre-test showed that 66,2% of mathematics teachers were able to correctly answer the questions, while the results of the post-test showed that 83,71% of mathematics teachers were able to correctly answer the same questions. Based on these data, it can be seen that GeoGebra training has increase the ability of mathematics teachers to understand the GeoGebra for geometry subjects by 17,5%.